Correlation Between Learning Activities and Student Learning Outcomes Using Problem-Based Learning at SMAN Mojoagung Jombang: Korelasi Antara Aktivitas Belajar Terhadap Hasil Belajar Siswa Menggunakan Problem Based Learning di SMAN Mojoagung Jombang - Fatikhatun Nikmatus Sholihah; Moch Faizul Huda; Muhamad Zainal Dwi Wahyudi; Afif Rifqi (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
This study aims to analyze the relationship between student activities in learning and cognitive learning outcomes. The method used in this research is a quantitative method with a correlational design. The population in this study were junior high school students, with a sample of class X-5 SMA Negeri Mojoagung Jombang using purposive sampling technique. Data was collected through observation of student activities and cognitive learning outcome tests. The results of the analysis show that there is a positive correlation between student activity and learning outcomes. This is indicated by a Pearson Correlation of 0.536 (moderate relationship) with a p-value of 0.001 which is smaller than 0.05, indicating a significant relationship. The Spearman Correlation is 0.578, which also shows a moderate but slightly stronger relationship. Since the correlation value between student activity and learning outcomes is within the range of 0.40 - 0.599, the relationship that occurs is in the moderate category. This means there is a relationship between student activity and learning outcomes. The implication of this research shows that increasing student involvement in the learning process can contribute to improving student learning outcomes